Biogenesis of Thylakoid Membranes in Chlamydomonas reinhardtii y1 (A Kinetic Study of Initial Greening). - White, R. A. (1994)
Initiation of thylakoid membrane assembly was examined in degreened cells of Chlamydomonas reinhardtii y1 cells depleted of thylakoid membranes and photosynthetic activity by growth in the dark for 3 to 4 d. Photoreductive activities of photosystem II (PSII) and photosystem I (PSI) increased with no apparent lag when degreened cells were exposed to light at 38[deg]C. However, fluorescence transients induced by actinic light, which reflect the functional state of PSII, changed only slightly during the first 2 h of greening. When these cells were treated with 3-(3,4-dichlorophenyl)-1,1-dimethyl urea (DCMU) or saturating light, fluorescence increased commensurate with the cellular content of chlorophyll. In similar experiments with greening cells of C. reinhardtii CC-2341 (ac-u-g-2.3), a PSI-minus strain, fluorescence increased with chlorophyll without treatment with DCMU. These data suggested that fluorescence of initial PSII centers in greening y1 cells was quenched by activity of PSI. Continuous monitoring of fluorescence in the presence or absence of DCMU showed that assembly of quenched PSII centers occurred within seconds after exposure of y1 cells to light. These results are consistent with initial assembly of PSI and PSII within localized domains, where their proximity allows efficient energy coupling.